SPECIFICS OF THE EDUCATIONAL PROCESS AND ITS IMPACT ON THE FORMATION OF THE PERSONALITY OF YOUNG CHILDREN SCHOOL AGE IN CONDITIONS OF DEPRIVATION - N.V. Sivoplyas (Academy of Cognitive and Natural Sciences, 2003)
No abstract.